Deformation Mechanism and Support Technology of Deep and High-Stress Soft Rock Roadway. (23rd March 2021) - Zheng, Lujing; Zuo, Yujun; Hu, Yafei; Wu, Wei
Abstract : In this study, the analysis and control of stability of surrounding rock in deep fractured soft rock roadway located in the underground mine of Jinfeng gold mine in Guizhou Province, China, has been investigated. The surrounding rock of roadway has been analyzed to characterize its deformation and failure mechanism through field survey, testing of rock physical and mechanical properties, in situ stress measure, analysis of mineral components of rock, and investigation of rock fragmentation degree. Based on the numerical simulation technology, the influence of different factors on the stability of roadway is studied. The physical and mechanical properties of surrounding rock and the bearing capacity of surrounding rock layer are to be improved to maintain the stability of broken soft rock roadway as high ground stress, rock fragmentation, and poor lithology leading to tunnel instability. Hence, a high-strength "cable bolt + fiber-reinforced shotcrete + steel mesh + split sets + resin bolt + cement grouting" combined support system has been proposed to improve the effective bearing structure significantly with high integrity and bearing capacity.